Radiative lifetime measurement of excited neutral nitrogen atoms by time resolved laser-induced breakdown spectroscopy - Haider, A F M Yusuf; Ira, Mehera Kamal; Khan, Z. H.; Abedin, K. M. (© 2014 Royal Society of Chemistry, 2017)
This article was published in the Journal of Analytical Atomic Spectrometry [© 2014 Royal Society of Chemistry] and the definite version is available at : 10.1039/c3ja50199j